Effortful control assessed by parental report and laboratory observation and adjustment in early childhood - Pereira,Ana Maria (2021)
Abstract Effortful control is a key aspect of children’s self-regulation showing a remarkable progress in early childhood. This study explored the relationship between effortful control, externalizing and internalizing problems and prosocial behaviour in young children. The sample was composed by 31 Portuguese children, aged between 3 and 6-years-old, and their parents. Effortful control was assessed by behavioural tasks (Tower of Patience, Bead Sorting) and the very short form of the Child Behavior Questionnaire administered to the parents. Internalizing and externalizing problems, as well as prosocial behaviour, were measured through the Strengths and Difficulties Questionnaire, answered by the parents. The results show that higher levels of effortful control are related to less externalizing problems and higher levels of prosocial behaviour. No significant associations were found between effortful control and internalizing problems. The mechanisms that may explain the different patterns of associations between effortful control and internalizing and externalizing problems in early childhood are discussed.